Pengaruh kepemimpinan kolaboratif dan kepuasan kerja terhadap kinerja guru - Nisrina Khalda Amini Madania Murod; Mohammad Shohib (Cognicia, 2022)
On teacher performance is one sign in evaluate the quality of the educational institutions. The performance of teachers also affect academic performance and the quality of students. Any of various factors affect performance of teachers both internally and externally. The purpose of this study was to find out how the influence of collaborative leadership and job satisfaction on teacher performance. This type of research is quantitative research with the sampling technique used is purposive sampling technique. The respondent's criteria are teachers who are more than 25 years old and have worked for at least 1 year and obtained 141 respondents. The data were then analyzed using multiple linear regression. The results showed that job satisfaction had a significant effect on teacher performance. Meanwhile, collaborative leadership style has no effect on teacher performance. However, leadership style and job satisfaction simultaneously have an influence on teacher performance. Principal leadership have an important role in managing schools and teacher job satisfaction is needed to improve teacher performance in schools. Keywords: collaborative   leadership,   job   satisfaction,   teacher   job performance